The Comparison of several earthquake decay models to predict the duration of aftershocks that occured in Manokwari Regency on April 21, 2012: Aftershock in Manokwari Regency on April 21, 2012 - Auwliyah Auwliyah; Sangaji Hasmi Maharani Ipa; Kristian Enggar Pamuji; Ishak Semuel Erari; Abdul Muis Muslimin (FMIPA Universitas Papua, 2025)
Has happen earthquake earth tectonics with magnitude 6.8 SR in Regency South Manokwari , West Papua Province on April 21, 2012. Purpose from study This is compare four decay models earthquake continuation namely the Omori , Mogi I, Mogi II and models Utsu to the earthquake data obtained from BMKG. Model with the smallest Root Means Square Error was the best earthquake decay model. Results matching curve shown the Mogi I and Utsu more suitable with earthquake decay data. Model of Mogi I and Utsu had mempredicted aftershocks for 15 days. Keyword: earthquake decay, aftershocks, Omori, Mogi I, Mogi II, Utsu